Geomorphic record of historical ferrous metallurgy in Mała Panew and Czarna River valleys (Poland) – Analysis of DEM from airborne LiDAR - Rutkiewicz, Paweł; Malik, Ireneusz; Gawior, Daniel; Woskowicz-Ślęzak, Beata; Kryszczuk, Paweł (AIP conference proceedings, 2017)
Ferrous metallurgy, through the centuries of its activity contributed the transformation of the natural landscape. We can find information on the time of functioning of iron works in historical sources. Among historians, there is an opinion that the traces of iron works activity are not visible in the field, but using GIS methods we can identify different types of objects related to ferrous metallurgy like dams, canals, smelter ponds and charcoal kilns. The aim of the study was to identify imprints of ferrous metallurgy in relief of two valleys in Southern Poland. The study was conducted in Mała Panew and Czarna River valleys where ferrous metallurgy, based on historical sources, has started in the 14th century and declined in the end of the 19th century. The tools used for identification objects related to ferrous metallurgy were standard shaded relief visualization techniques. We created models of terrain elevation with hillshading and spatial density of 0.2 m. During the analysis of DEM images we detected objects interpreted as traces of smelter ponds with accompanying dams and canals, and oval objects recognized as remnants of charcoal kilns. Large number and vast distribution of relief features related to ferrous metallurgy, charcoal kilns in particular, clearly indicate that the historical smelting and ironwork activity natural environment of studied areas was transformed. Relief of valley floors, in particular, was a subject of change.